Концептуальне моделювання та формалізація ієрархічних знань для систем підтримки прийняття рішень - Заговора, А. Ю. (ХНУРЕ, 2025)
This paper is devoted to the conceptual modeling and formalization of knowledge for decision support systems (DSS). The study examines the hierarchical structure of knowledge representation, which enables efficient structuring of complex domains. The application of category theory allows for the modeling of relationships between concepts, facilІТating the development of adaptive and flexible knowledge bases. The results confirm the effectiveness of the proposed approach in optimizing DSS performance under dynamic condІТions.
Keywords: концептуальне моделювання; ієрархічне знання; підтримка рішень